Scalable routing in mobile ad hoc networks - Yang, Peng (2008)
In this thesis, we focus on the scalability study on the routing in MANETS. We analyze the existing routing approaches in MANETs, we conclude that clustering and hierarchical routing are promising ways to improve the scalability of the routing based on the analysis. We propose an adaptive clustering scheme (RMACP: adaptive&cached cluster-based routing protocol) to reduce the maintenance overhead for clustering schemes. Simulation results show that without any routing performance degradation the RMACP can achieve much lower control overhead compared with other existing clustering techniques.